THE IMPACT OF INTERNATIONAL MIGRATION ON THE LABOR MARKET – A CASE STUDY FROM HUNGARY - Oláh, Judit; Halasi, György; Szakály, Zoltán; Popp, József; Balogh, Péter (Amfiteatru economic, 2017)
The economic, political and social changes experienced globally in recent years have influenced international migration in various countries. The aim of our study is to present the economic and non-economic aspects which determine the quantitative evaluation of migration and to reveal which of the two main factor groups is more dominant. In January 2017, an online questionnaire survey was conducted on the subject of migration. The group of respondents consisted of 438 full-time BSc, MSc and PhD students in Hungarian higher education institutions. Based on these questionnaires, two independent samples t-test, and one-way ANOVA, factor analysis and binary logistic regression procedures were performed.Based on the findings obtained, it was concluded that anti-migration behaviour cannot be explicitly explained by its economic impacts on the labour market. The rejecting attitudes observed on behalf of certain respondents were not in significant correlation with their highest educational levels or their given social class. As a result of the statistical analysis performed, it was concluded that the integration of foreigners is hindered by the so-called socio-cultural barriers, which cannot be removed solely by economic policy measures. Social conflicts of interest have to be eliminated in order for migration to have an active and permanently positive impact on the economy.